THE PECULIARITIES IN O-TYPE GALAXY CLUSTERS - Panko, E. A.; Emelyanov, S. I. (Одеські астрономічні публікації, 2017)
We present the results of analysis of 2D distribution of galaxies in galaxy cluster ﬁelds. The Catalogue of Galaxy Clusters and Groups PF (Panko & Flin) was used as input observational data set. We selected open rich PF galaxy clusters, containing 100 and more galaxies for our study. According to Panko classiﬁcation scheme open galaxy clusters (O-type) have no concentration to the cluster center. The data set contains both pure O-type clusters and O-type clusters with overdence belts, namely OL and OF types. According to Rood & Sastry and Struble & Rood ideas, the open galaxy clusters are the beginning stage of cluster evolution. We found in the O-type clusters some types of statistically signiﬁcant regular peculiarities, such as two crossed belts or curved strip. We suppose founded features connected with galaxy clusters evolution and the distribution of DM inside the clusters.